Local Perception on the Climate Change in Nepali Society: A Spatial Comparison between Urban and Rural Area of Dharan and Bhojpur in Nepal - Sharma, Bigyan; Subedi, Shukra Raj (Dristikon: A Multidisciplinary Journal, 2022)
Climate change has become a global concern and debatable issue worldwide in the present era. It needs to be discussed from rural community and urban perspective in terms of the local understanding, experience, and knowledge in environmental discourse. The local understanding on climate change in Nepali society is the spatial comparative analysis of understanding to the environment from the perspective of local people. Being spatial comparative studies, it compares the understanding of environmental change of people among rural and urban areas Province 1 of Nepal. It underpins the interpretive research philosophy based on the qualitative research approach, employing the convenience sampling of non-probability sampling design with in-depth interview, and observation as the tools of data collection. The six research informants, three from the rural areas of Temkemaiyum of Bhojpur district and three from the urban areas of Dharan Sub-metropolitan City of Sunsari district have selected for the perception and experience collection for the comparative study. The finding has revealed that the both people of urban and rural areas are noticing the climate change. However, their understanding has varied based their knowledge, understanding, and experience. Though the study has focused on climate change, it has been recommended for researchers, policy makers, and policy implementers for environmental discourse in further research in Nepalese context.